EFECTO ANTIBIOTICO PARA RHIZOBIUM DE UNA FRACCION ORGANICA DEL SUELO - CASAS CAMPILLO, CARLOS (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
Results are recorded of the best substrates for growth of Clostridium and fermentation of butanol-acetone Best media are: peptic digest of parota seed (Enterolobium cyclocarpum) with or without thio-glycolate, parota mash, rye medium, orange juice, papay
CIENC MEX
Keywords: EFECTO ANTIBIOTICO, RHIZOBIUM, FRACCION ORGANICA, SUELO; MULTIDISCIPLINARIA; MICROBIOLOGIA; ANTIBIOTICOS